Specific PCR Primers Based on Cytochrome-b Gene for Molecular Detection of Javan Mongoose (Herpestes javanicus) - Sena Adi Subrata; Subeno Subeno; Atus Syahbudin (Jurnal Ilmu Kehutanan)
Javan Mongoose is a meso-carnivore species that have an important role in ecosystem as a predator. It is believed that its occurrence controls prey populations including some pest species. However, the belief is an anecdote because of lacking supportive data. Difficulty in visually observing the species is a major problem preventing data collection. This study aims to design PCR primer for detecting the Mongoose molecularly from organic material remaining, such as feces. The design starts with selecting specific marker from 51 DNA sequences of cytochrome-b. The DNA sequences were of 19 Javan carnivore collected from GenBank (NCBI). PCR primers were designed and tested using both in-silico and in-vitro techniques. The sequence collection and selection, and primer design process employed MEGA 5 and SP-Designer software. We successfully designed PCR primers: forward 5’- CAAATCACACCCACTCATTAAAATC-3’ dan reverse 5’-TGTGGGTTACTGATGAAAAGG-3’. The primer is capable of detecting Javan Mongoose from remaining organic material. The study contributed to basic data collection of Javan Mongoose for advanced studies such as occupancy modeling, species distribution modeling and diet analysis. This information is fundamental for understanding the role of the Javan Mongoose in an ecosystem.